Ceres Crater Degradation Inferred From Concentric Fracturing. Issue 5 (6th May 2019) - Otto, K. A.; Marchi, S.; Trowbridge, A.; Melosh, H. J.; Sizemore, H. G.
Abstract: The dwarf planet Ceres exhibits a collection of craters that possess concentric fractures beyond the crater rim. These fractures typically range from a few hundred meters to a few kilometers in length and are less than 300 m wide. They occur preferentially on elevated regions around the crater and are located less than a crater radius beyond the rim. In total there are 17 craters exhibiting concentric fracturing beyond the rim. They are located in the midlatitudes. The craters' diameters range between 20 and 270 km. We investigate the concentric fractures of three craters (Azacca, Ikapati, and Occator) in detail and suggest that the formation of such concentric fractures can be explained by a shallow (<10‐km) low‐viscosity (~10 20 ‐Pa·s) subsurface layer extending underneath the crater and its surroundings. Finite element modeling of such a scenario applied to a typical concentrically fractured crater of 50‐km diameter implies that the depth of the low‐viscosity layer is comparable to the crater depth and the layer does not extend to the surface. Given that not every crater of comparable size on Ceres exhibits concentric fractures, it is also suggested that these conditions are only met locally and may be related to the surface temperature. Correlations of concentrically fractured craters with other volatile related features, such as pitted terrains and floor fracturing, suggest that the low‐viscosity subsurface layer may be enriched in ice. Plain Language Summary: The dwarf planet Ceres has recently been visited by the Dawn spacecraft, which was able to take high‐resolution images of Ceres' surface (~35 m/pixel). These images show that small concentric fractures surround some craters, at distances of up to one crater radius external to the craters' rims. Such fractured craters seem to be unique to Ceres. We investigate the appearance of these fractures and how they may have formed. Previous investigations of Ceres' composition have found that Ceres may possess water ice or salt in its upper layers. We suggest that a deformable, possibly ice‐rich or salt‐rich, layer under the concentrically fractured craters may have formed the fractures. The weight of the material overlying such a layer over long timescales (60 Myr) may deform it, producing near‐surface stresses that cause fracturing. We find that certain conditions (e.g., a layer less than 10 km below the surface, with a thickness of a few kilometers) are more likely to form fractures, and the presence of concentric fracturing therefore hints at the distribution of ice or salt in Ceres' subsurface. Key Points: We analyzed craters on Ceres with concentric fracturing We model the relaxation of a low‐viscosity subsurface layer to explain the observed fracturing The degradation of craters on Ceres may locally be influenced by low‐viscosity material in the subsurface